Feminism, Philosophy of Science, and Their Influence on Women's Language - Srisna J. Lahay (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2022)
In this paper, the writer aims to delineate the relationship between feminism, philosophy of science, and women’s language. In her description, the writer refers to scientific works about feminism, philosophy, language, and gender as well as her research about gossip, conducted for her Master’s degree at Universitas Katolik Indonesia (Unika) Atma Jaya, Jakarta. In this paper, the writer first discusses sex, gender, and feminism. Next, the writer describes the relationship between feminism and the philosophy of science. The writer later examines the relationship between feminism and language as well as studies about those topics. Later, the writer describes her research about gossip among female participants, conducted on the data from the U.S. TV series, Sex and the City, and based on the model of analysis proposed by Jennifer Coates. In the end, the writer states that feminism, a school of thought as well as a social, political, and cultural movement contesting the inequality of women, has developed from the thoughts of philosophers and later influenced the development of science and research about language and gender and that the use of language by women and the reality of women, formed by their use of the language, can hopefully be better understood and that this understanding can better help in the execution of researches about women’s language.